Glyceraldehyde-3-phosphate dehydrogenase of Paracoccidioides brasiliensis is a cell surface protein involved in fungal adhesion to extracellular matrix proteins and interaction with cells - Barbosa, M. S.; Bao, S. N.; Andreotti, P. F.; de Faria, F. P.; Felipe, M. S. S.; Feitosa, L. D.; Mendes-Giannini, Maria José Soares [UNESP]; Soares, C. M. D. (Amer Soc Microbiology, 2006)
The pathogenic fungus Paracoccidioides brasiliensis causes paracoccidioidomycosis, a pulmonary mycosis acquired by inhalation of fungal airborne propagules, which may disseminate to several organs and tissues, leading to a severe form of the disease. Adhesion to and invasion of host cells are essential steps involved in the infection and dissemination of pathogens. Furthermore, pathogens use their surface molecules to bind to host extracellular matrix components to establish infection. Here, we report the characterization of the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) of P. brasiliensis as an adhesin, which can be related to fungus adhesion and invasion. The P. brasiliensis GAPDH was overexpressed in Escherichia coli, and polyclonal antibody against this protein was obtained. By immunoelectron microscopy and Western blot analysis, GAPDH was detected in the cytoplasm and the cell wall of the yeast phase of P. brasiliensis. The recombinant GAPDH was found to bind to fibronectin, laminin, and type I collagen in ligand far-Western blot assays. of special note, the treatment of P. brasiliensis yeast cells with anti-GAPDH polyclonal antibody and the incubation of pneumocytes with the recombinant protein promoted inhibition of adherence and internalization of P. brasiliensis to those in vitro-cultured cells. These observations indicate that the cell wall-associated form of the GAPDH in P. brasiliensis could be involved in mediating binding of fungal cells to fibronectin, type I collagen, and laminin, thus contributing to the adhesion of the microorganism to host tissues and to the dissemination of infection.